Producing Space, Tracing Authority: Mapping the 2007 San Diego Wildfires. (June 2014) - Petersen, Katrina
This article explores the materiality of disaster politics through the practice of mapping during the 2007 wildfires in Southern California. It examines the process of production of two different maps, the maps produced by San Diego County and a popular Google My Map created by local media and academic institutions, in order to explore how an unfolding disaster comes to be understood. This article argues that the interplay between different technological and human entities to produce each map in turn produced different spaces of disaster in ways that challenged priorities of disaster preparedness and response. Specifically, the different mapping practices in 2007 produced different relationships to temporality, boundaries and responsibility, making different aspects of the disaster visible while constructing different threats and definitions of danger. They juxtaposed representational and relational knowledge as well as the value of prevention and demonstration. This article draws on data collected through textual analysis of government and scientific documents as well as interviews and observations of key actors, their mapping practices, and socio-technological networks.